2010
DOI: 10.1007/s00213-010-2120-4
|View full text |Cite
|
Sign up to set email alerts
|

The cannabinergic system is implicated in the upregulation of central NGF protein by psychotropic drugs

Abstract: The cannabinergic system is implicated in the mechanisms of action of certain psychotropic drugs including the upregulation of brain NGF levels. This provides a better understanding of the pathophysiological mechanisms underlying neuropsychiatric disorders, leading to novel drug design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…The reduced expression of neurotrophins in tissues, serum and plasma has been demonstrated through the normalization of these values after clinical treatment (Hashimoto, 2010;Hassanzadeh and Rahimpour, 2011).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The reduced expression of neurotrophins in tissues, serum and plasma has been demonstrated through the normalization of these values after clinical treatment (Hashimoto, 2010;Hassanzadeh and Rahimpour, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…In an experimental study, chronic treatment with nortriptyline and citalopram antidepressants increased brain NGF levels (Hassanzadeh and Rahimpour, 2011). On the other hand, Martino et al (2013) demonstrated that patients with MDD had NGF serum levels reduced when compared with healthy controls, not being reversed by duloxetine antidepressant, possibly reflecting functional impairment in the adaptive neuroplasticity of stress in depressive disorders (Martino et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We found no association between suicide risk and NGF levels; one possible explanation might be the characteristics of our sample, in which almost no one was taking any medication and probably was seeking attendance for the first time. However, treatment with antidepressants and electroconvulsive therapy increased NGF levels in both clinical and experimental studies 44,45. The psychopathology that was more prevalent included MDD, and the pathogenesis of these disorders is related to the regulation of multiple neurotrophic factors and associated NGF levels decreased in the early stages 46.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the lack of a control for the use of treatments of mood disorders, including antipsychotic and other medications, could have influenced the results 2931. In addition, psychotic symptoms and cognitive impairments were not assessed.…”
Section: Discussionmentioning
confidence: 99%